The Gulf-Israeli normalization, Causes and Results - Dalian, Lecturer. Dr. Enas Mijbel (The International and Political Journal, 2023)
For several decades, the Arab region has witnessed Western pressure to normalize Arab-Israeli relations. These pressures come in the context of the Western commitment to support Israel and led to the launch of the settlement process with Egypt in 1978, then the Palestinian Authority and Jordan in 1993 and 1994. However, the path did not produce many processes of reintegrating ‘Israel’ into the Arab region. After the American occupation of Iraq in 2003, most Arab countries found themselves facing internal and regional pressure to accept American offers for normalization with Israel. The so-called ‘Deal of the Century’ 2018-2020 is the largest step through which the United States sought to integrate ‘Israel’ into the region. This deal was marketed under the title of the existence of common regional threats that require normalization and cooperation, and it resulted in the accepting of four Arab countries: the Emirates, Bahrain, Sudan, and Morocco. This normalization process may lead to one of the following possibilities: Ending the existence of the Palestinian issue and accelerating the emergence of ‘Israel’ as a state integrated into the Arab regional system. The failure of the process of integrating “Israel” into the region and the re-emergence of the Arab-Israeli conflict. The continuation of the Palestinian issue for a longer period due to the complications associated with it. The last option is the most likely, despite the ongoing political and media obfuscation attempts on the Palestinian issue in the short run.